The Driving Factors of GrSCM Adoption for Indonesian Electronic Industry - Masudin, Ilyas; Jakfar, Akhmad; Zulfikarijah, Fien (International Journal of Engineering and Technology, 2019)
The application of Green Supply Chain Management (GrSCM) appears because of the increased awareness of the environmental impact of industrial development. GrSCM progress as anÂ innovation environment that integrate environmental factors into supply chain management.Â Thus the company began to shift from traditional supply chain to green supply chain management. This studyÂ is focused on the development of GSCM in term of determining the driving factors affecting the adoption of GrSCM. Factor analysis is used to find the key factors considered in GrSCM implementation in Indonesian electronic industry.Â Results of this study can be identifiedÂ that there are seven factors affecting the adoption of green supply chain management for electronic industry in Indonesia such as green procurement, waste management; green distribution, green marketing; green manufacturing, green design, and green environment.Â Â